A review of ethnobotany, phytochemistry, antimicrobial pharmacology and toxicology of Nigella sativa L. - Hossain, Md. Sanower; Sharfaraz, Ashik; Dutta, Amit; Ahsan, Asif; Masud, Md. Anwarul; Ahmed, Idris Adewale; Goh, Bey Hing; Urbi, Zannat; Sarker, Md. Moklesur Rahman; Ming, Long Chiau (Elsevier Ltd, 2021)
Nigella sativa L. is one of the most extensively used traditional medicinal plants. This widely studied plant is known to display diverse pharmacological actions, including antimicrobial activities. Current literature has documented its multi-target mode of antimicrobial actions. N. sativa or its bioactive compounds, such as thymoquinone, can induce oxidative stress, cell apoptosis (by producing reactive oxygen species), increase membrane permeability, inhibit efflux pumps, and impose strong biocidal actions. Despite its well-documented antimicrobial efficacy in the experimental model, to the best of our knowledge its antimicrobial mechanisms highlighting the multi-targeting properties have yet to be well discussed. Is N. sativa or thymoquinone a valuable lead compound for therapeutic development for infectious diseases? Are N. sativa’s bioactive compounds potential antimicrobial agents or able to overcome antimicrobial resistance? This review aims to discuss the antimicrobial pharmacology of N. sativa-based treatments. Additionally, it provides a holistic overview of the ethnobotany, ethnopharmacology, and phytochemistry of N. sativa.